Substrate Effect on Plasma Clean Efficiency in Plasma Enhanced Chemical Vapor Deposition System - Shiu-Ko JangJian; Ying-Lang Wang (Active and Passive Electronic Components)
The plasma clean in a plasma-enhanced chemical vapor deposition (PECVD) system plays an important role to ensure the same chamber condition after numerous film depositions. The periodic and applicable plasma clean in deposition chamber also increases wafer yield due to less defect produced during the deposition process. In this study, the plasma clean rate (PCR) of silicon oxide is investigated after the silicon nitride deposited on Cu and silicon oxide substrates by remote plasma system (RPS), respectively. The experimental results show that the PCR drastically decreases with Cu substrate compared to that with silicon oxide substrate after numerous silicon nitride depositions. To understand the substrate effect on PCR, the surface element analysis and bonding configuration are executed by X-ray photoelectron spectroscopy (XPS). The high resolution inductively coupled plasma mass spectrometer (HR-ICP-MS) is used to analyze microelement of metal ions on the surface of shower head in the PECVD chamber. According to Cu substrate, the results show that micro Cu ion and the CuOx bonding can be detected on the surface of shower head. The Cu ion contamination might grab the fluorine radicals produced by NF3 ddissociation in the RPS and that induces the drastic decrease on PCR.